Autobiographical memory in contact tracing: evidence from the COVID-19 pandemic - Rossi-Arnaud, Clelia; Mastroberardino, Serena; Spataro, Pietro; Santirocchi, Alessandro; Alessi, Federica; Naser, Aicia; Pesola, Maria Chiara; Cestari, Vincenzo (Frontiers in Psychology, 2023)
The COVID-19 pandemic that has affected the world's population has compelled various governments to trace all contacts of a confirmed case, as well as to identify the locations visited by infected individuals. This task, which requires the activation of our autobiographical memories, can make a difference in the spread of the contagion, and was based primarily on telephone interviews with infected people. In this study, we examined whether participants were able to provide contact tracing information by asking them to fill in an online standardized form in which they recounted every day of the two weeks before, reporting as much information as possible. The time period selected included, among other things, the day on which the Italian government issued the decree initiating the COVID-19 lockdown. The task was completed twice, the first time relying solely on their memory, and the second time also using external aids (diaries, mobile phones etc.). Reports were then coded using a scheme that segmented accounts into informational details, divided into two broad categories, internal and external. Results showed that i) using external aids was effective when participants had to recall the day furthest away or if to-be-recalled events have low distinctiveness, and ii) memories of internal details were generally better recalled than memories of external details.Participants were overall accurate and reported a large amount of information about people and places they visited, although, because of the connection with key pandemic-related events, the effect was somewhat stronger on specific days (e.g., the day the lockdown was announced). The results of this work could provide a useful tool for improving the design of contact tracing procedures in the event of an unwanted future public health crisis caused by a highly infectious agent.